INTEGRATION OF GEOGEBRA-BASED DIRECT LEARNING MODELS: IMPLEMENTATION IN MATHEMATICS LEARNING - Sumarauw, Stefani Jully; Wenas, John R.; Sumarauw, Sylvia J. A. (LPPM Universitas Bina Bangsa, 2024)
Teachers need to integrate applications/media into mathematics learning to improve the quality of mathematics learning. Initial observation results show that teachers in the learning process only use direct learning models without involving learning media that can attract students' interest in learning. This results in low student learning outcomes in Tangent Lines to Circles material. One application that can be used as a mathematics learning medium is the GeoGebra application. This research aims to describe the learning outcomes of class VIII students at SMP N 1 Eris on Tangent Lines to Circles material taught using the direct learning model with the GeoGebra application, which is better than the learning outcomes of students taught using the direct learning model without the GeoGebra application. The research subjects were class VIIIA as an experimental class (a class that used a direct learning model with the GeoGebra application) consisting of 20 students and class VIIIB as a control class (a class that used a direct learning model) composed of 20 students. The instrument used in this research is a test in the form of essay questions to measure student learning outcomes. The data collection technique is to give a pretest and posttest in the form of descriptive questions consisting of 5 questions. Based on the research results, it can be concluded that learning using the direct learning model with the GeoGebra application on circle tangent material in class VIII students at SMP Negeri 1 Eris is better than learning using the direct learning model without the GeoGebra application